Expression of epigenetic marker EZH2 in squamous cell carcinoma of skin - Shams, Muhammad Usman; Abdul Hannan Nagi,; Saqib Mehmood,; Nausheen Henna, (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the frequency and level of expression of enhancer of zeste homologue 2 in cutaneous squamous cell carcinoma, and compare then with normal skin. Method: The retrospective, descriptive study was conducted at the Department of Morbid Anatomy and Histopathology, University of Health Sciences, Lahore, Pakistan, and comprised data from January 2016 to April 2023 related to cutaneous squamous cell carcinoma in group A and normal skin cases in group B that were evaluated and compared for enhancer of zeste homologue 2 immunohistochemistry expression and positivity. Group A cases with increased immunohistochemistry expression were tested by fluorescence in situ hybridisation for enhancer of zeste homologue 2 amplification. Data was analysed using SPSS 22. Results: Of the 60 patients, 30(50%) were in group A; 19(63.3%) males and 11(36.7%) females with mean age 48±16.5 years. There were 30(50%) patients in group B; 29(96.7%) females and 1(0.3%) male with mean age 47.6±11.3 years. There were 25(83.3%) well-differentiated cases in group A. Enhancer of zeste homologue 2 positivity was noted in 25(83.3%) case in group A compared to 6(20%) in group B (p<0.001). The enhancer of zeste homologue 2 expression level was also significantly higher in group A than group B (p<0.001). Immunohistochemistry overexpression of enhancer of zeste homologue 2 was found in 13(43.3%) group A cases, and, of them, 6(46.15%) showed enhancer of zeste homologue 2 amplification. Conclusion: Enhancer of zeste homologue 2 overexpression was noted in cutaneous squamous cell carcinoma cases, indicating that enhancer of zeste homologue 2 had a potential role in cutaneous squamous cell carcinoma tumourigenesis. Key Words: EZH2 protein, Human, Immunohistochemistry, IHC, In situ hybridisation, Fluorescence, FISH, Squamous cell carcinoma, Skin neoplasms.